0184 How to achieve effective results when filming in a clinical environment for research. (2nd November 2015) - Riby, Stuart; Graby, Matthew; Gay, Christopher
Abstract : Background/context: Simulation centres are an ideal environment to control and host research but as the quest for more and more evidence of the effectiveness of simulation training increases there is a growing need to compare what is learnt in the sim centre back on the ward as part of research projects. Filming of research can be an effective tool but if done below the standards needed from a technical point of view or if it breaches patient dignity and confidentially it can have an extremely negative outcome for any project. Description of innovation/topic: Having taken part in various research projects and having much experience of filming in clinical environments and through our own and others successes and failures we hope to offer advice, tips and technical advice on how to prepare for the best possible outcome when filming in a clinical environment. Improvements/outcomes: We will covera wide range of topics from technical to non-technical - Preparation Hardware/equipment Filming and audio positioning Consent Confidentiality Patient dignity Discretion Communication with staff/patients/relatives Editing software/techniques Filming techniques Anonymisation End product Our experience Take home messages: To give people an insight into all the different factors to be considered when filming in a clinical environment. It isn't just about turning up with a camera.... To give people the knowledge and confidence to create successful and effective videos for research. To highlight the importance video can be as a medium in clinical research. Time is precious in a clinical environment and it is essential not to disturb the activity that is happening as you will not be welcomed back. Get it right first time and be discreet.